Implementation Of Problem Solving Methods For Improving Student Motivation In Sociology Subject Class Xi Ips 4 At Man Jombang - Siamah, Siamah; Rahmania, Nita; muharyati, Yully; Firmansyah, Edi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
As known reality that occurs in MAN Jombang in class XI IPS 4 students are still not optimal in responding subjects Sociology given by the teacher. Such as, lack of motivation the student, the teacher whose methods are less variable, while noisy student learning, lack of attention, and ignore the sociological subjects. On the basis of the fact that education occurs, investigators will present the implementing of problem solving methods for improving student motivation in Sociology subject class XI IPS 4 at MAN Jombang. Researchers chose the site because you want to apply a form of problem solving methods.The purpose of this study was to describe the planning, implementation of learning using problem solving methods to improve students' motivation XI IPS 4 in MAN Jombang With the design of collaborative classroom Action Research type. Data collection techniques were used, namely: (1) observation, (2) interviews, (3) documentation. Mechanical analysis of qualitative data consisting of observations and documentation analyzed qualitative description, while the data is numeric or quantitative data were analyzed by calculating the percentage and average.The study's findings indicate that the authors offer methods of learning can improve student motivation especially on the subjects of Sociology. Increased motivation on problem solving methods first cycle on average 2.94 (less), increased to 3.95 in the second cycle (enough), the third cycle increases the average to 4.00 (good), and the fourth cycle ride be 4.03 (good).